PENGARUH VARIABEL PERCEIVED USEFULNESS, TRUST, CONSUMER SATISFACTION, DAN INTENTION TO USE PADA PENGGUNAAN APLIKASI INSTAGRAM SEBAGAI MEDIA TRANSAKSI JUAL BELI - Alkent Alkent; Rinabi Tanamal (Universitas Bunda Mulia, 2020)
Along with the development of technology, lifestyle follows. The use social media as a medium of transaction, Instagram is one of them. Thus, came this research in regard in Trust, Perceived usefulness, Consumer Satisfaction that used as a reference for research on User’s of Instagram that are known to use the application for the needs of selling and buying through the Instagram. Data collection using questionnaire method and collected as much as 152 respondents and use accidental sample technique and sample consideration. After that tested the validity andreliability test using SPSS. The data shows that Trust (TU) variable gives positive value of 0.879 to Perceived Usefulness (PU) and positive effect of 0,596 on Consumer Satisfaction (CS) while Perceived Usefulness (PU) gives positive value 0,930 to Intention to Use (ITU) and Consumer Satisfaction (CS) gives positive value to Intention to Use (ITU). It can be concluded that Trust, Consumer Satisfaction, (Perceived Usefulness gives a positive influence on the use of Instagram application as a medium of buying and selling transaction.Keywords: Trust, Perceived Usefulness, Consumer Satisfaction, Technology Acceptance Model (TAM).